Aluminum Exposure from Parenteral Nutrition: Early Bile Canaliculus Changes of the Hepatocyte with A 2021 Update on the 2019 Technical Report of the American Academy of Pediatrics on Aluminum Effects in Infants and Children - Amanda R. Hall; Ha Le; Chris Arnold; Janet Brunton; Robert Bertolo; Grant G. Miller; Gordon A. Zello; Consolato Sergi (Current Topics in Medicine and Medical Research Vol. 13, 2021)
Background: Neonates on long-term parenteral nutrition (PN) may develop parenteral nutrition-associated liver disease (PNALD). Aluminum (Al) is a known contaminant of infant PN, and we hypothesize that it substantially contributes to PNALD. In this study, we aim to assess the impact of Al on hepatocytes in a piglet model. Methods: We conducted a randomized control trial using a Yucatan piglet PN model. Piglets, aged 3-6 days, were placed into two groups. The high Al group (n=8) received PN with 63 µg/kg/day of Al, while the low Al group (n=7) received PN with 24 µg/kg/day of Al. Serum samples for total bile acids (TBA) were collected over two weeks, and liver tissue was obtained at the end of the experiment. Bile canaliculus morphometry was studied by transmission electron microscopy (TEM) and Image-J software analysis. In December 2019, the American Academy of Pediatrics issued a key technical report on Al effects in infants and children. This report was revised and commented on in this chapter. Results: The canalicular space was smaller, and the microvilli were shorter in the high Al group than in the low Al group. There was no difference in the TBA between the groups. Conclusions: Al causes structural changes in the hepatocytes despite unaltered serum bile acids. High Al in PN is associated with short microvilli, which could decrease the functional excretion area of the hepatocytes and impair bile flow. Long-term toxicity studies from the Al content in PN components supported the US Food and Drug Administration (FDA) in the decision to implement specific rules. It has been required that large-volume ingredients reduce the Al concentration and all small volume components be specifically labeled with the Al concentration. However, both US FDA and we consider that despite these rules, the total Al concentration from some components remains above the recommended final concentration. US FDA and our concerns about toxicity from the Al present in infant PN formulas are grounded, requiring more research on this topic.